Analyzing Human and ChatGPT Responses: A Comparative Study of Transformer Models in Natural Language Processing - Gokcimen, Tunahan; Das, Bihter (Institute of Electrical and Electronics Engineers Inc., 2023)
With the latest developments in artificial intelligence, language models have reached the level that can produce human-like responses. One of the most successful examples of these technologies is the GPT-3 language model developed by OpenAI. This study aims to investigate how similar human responses and artificial intelligence responses are, and which transformer model performs best. In the study, a series of questions were answered using different transformer-based models and compared with the answers given by humans. The highest performance was obtained with the roberta-base-openai-detector model. This study provides researchers with a different perspective to understand the difference between artificial intelligence technologies and human responses. © 2023 IEEE.
4th International Informatics and Software Engineering Conference, IISEC 2023 -- 21 December 2023 through 22 December 2023 -- Ankara -- 196814
Keywords: ChatGPT; Human-like responses; NLP; OpenAI; transformer-based models